Neospora caninum en llamas de Huancavelica, Perú - Pilco, Marelsy Pilco (2018)
The aim of this study was to determine, through the Indirect Immunofluorescence (IFAT) technique, the frequency of antibodies against Neospora caninum in llamas from the Livestock Association of Lachocc, Huancavelica. Blood samples were taken from 98 adult female llamas, older than one year. The sera were analysed by IFAT using a cut-off point of 1:100. The positive sera were titrated with serial dilutions, determining a frequency of antibodies against N. caninum of 12.2% (12/98). Of the 12 positive sera, 75.0% (9) had titres of 1:100, 16.7% (2) with 1:200 and 8.3% (1) with 1:400. No significant association was found between the variables age, history of abortions and parity with the presentation of seroreactors to N. caninum.